Gummosis, Brown Spot and Seedling Mortality in Su-babul 2. Epidemiology and Control of the Disease - Singh, Sujan; Khan, S. N.; Misra, B. M. (Indian Forester, 1983)
The paper deals with studies on epidemiology and cuntrol of gummosis, brown spot and seedling mortality of Su-babul in plantations caused by Fusarium semirecium. Studies revealed that nearly 50 per cent of the seeds collected from diseased planlation were infected by the disease pathogen and 70 percent infected seeds either failed to germinate or seedlings were killed within 60 day after germination. Only 13 percent of diseased seeds grew into diseased plants. Primary infection on Sub-babul was found to take place from collateral bosts infected by F. semitectum and occurring withia Sub-babul plantations. Ten collateral hosts namely Cassia fistula. C. tora, Cymhopogon citrutus, Cyperus rotundis, Dendracalamus strictus, Diospyros melanoxylon, Gynodropsis sp , Lantana camara, Murraya koenigli and Sacchorum munja were found infected by F. semetectum in sub-babul plantations. Pathogenicity of the isolates of F. semitectum obtnained from most of the above hosts was confirmed by inoculation experiments. All the above hosts, Dendrocalamus vulgare and Mollocanna baecifera were found as new host records for F. semitectum. Subsequent spread of gnmmosis and canker disease in Sub-babul plantations was found through spores produced on infected seeds, pods and twigs fallen on the ground and through contact of juvenile parts of Su-babul plants with infected Parts of the adjoining diseased plants. Main disease sread was found to take place during first two years of the plantations. While disease spread within plants continued through out the year, plant to plant spread was found to have taken place during monsoon months only. Infection of F. semitectum in Sub-babul seeds was effectively eradicated by giving a 15 minutes dip treatment to infected seeds in 0.1 per cent solutiDn of emisan (Methoxy ethyl mercury chloride) containing 6 per cent mercury. Disease development and spread effectivelly checked by conducting two weedings one in July and the other in October up to 0.3 m radius around the plants along with pruning of lower branches upto one third of plant height during first two yeas of plantation growth.